Impact of mass atresia in reproductive ecology, maturity ogive, spawning migration and population dynamics on S. mentella and S. marinus in Icelandic waters - Saborido-Rey, Fran; Murua, Hilario; Garabana, Dolores; Sigurdsson, Thorsteinn (2005)
ICES Annual Science Conference, 20-24 September 2005, Aberdeen, UK Generalized or mass atresia in determinate spawners fish is not well documented, although has been reported in some species. In redfish, has been rarely studied, but in this paper it is known that mass atresia is a common feature in the two main redfish species inhabiting Icelandic waters. Mass atresia has been observed both at previtellogenic stage and during vitellogenesis. Its presence during vitellogenesis means unavoidable that that fish will not spawn, since there is not sufficient time to develop another clutch of oocytes. Oocyte development in relation with atresia intensity has been studied along the year and in different areas around Iceland to study its impact on: a) The reproductive strategies of the species regarding maturation, ripening and the condition factor. b) Skip spawners are not immature fish, but inactive since they are not contributing to egg production. Thus, different maturity ogives can be built with drastic difference between them. Since inactive mature females may look macroscopically as immature, important historical errors have been found when comparing size at maturity among areas or species. c) In Iceland redfish migrates for maturing and spawning. Mass atresia affects to the migration pattern, since first time spawners failing to mature and skip spawners remain in the origin area and do not migrate. d) The impact of the above mentioned features on population dynamic and survey estimation is further discussed No